Coumarins as Fungal Metabolites with Potential Medicinal Properties - Olga M. Tsivileva; Oleg V. Koftin; Nina V. Evseeva (MDPI AG, 2022)
Coumarins are a structurally varied set of 2H-chromen-2-one compounds categorized also as members of the benzopyrone group of secondary metabolites. Coumarin derivatives attract interest owing to their wide practical application and the unique reactivity of fused benzene and pyrone ring systems in molecular structure. Coumarins have their own specific fingerprints as antiviral, antimicrobial, antioxidant, anti-inflammatory, antiadipogenic, cytotoxic, apoptosis, antitumor, antitubercular, and cytotoxicity agents. Natural products have played an essential role in filling the pharmaceutical pipeline for thousands of years. Biological effects of natural coumarins have laid the basis of low-toxic and highly effective drugs. Presently, more than 1300 coumarins have been identified in plants, bacteria, and fungi. Fungi as cultivated microbes have provided many of the nature-inspired syntheses of chemically diverse drugs. Endophytic fungi bioactivities attract interest, with applications in fields as diverse as cancer and neuronal injury or degeneration, microbial and parasitic infections, and others. Fungal mycelia produce several classes of bioactive molecules, including a wide group of coumarins. Of promise are further studies of conditions and products of the natural and synthetic coumarins' biotransformation by the fungal cultures, aimed at solving the urgent problem of searching for materials for biomedical engineering. The present review evaluates the fungal coumarins, their structure-related peculiarities, and their future therapeutic potential. Special emphasis has been placed on the coumarins successfully bioprospected from fungi, whereas an industry demand for the same coumarins earlier found in plants has faced hurdles. Considerable attention has also been paid to some aspects of the molecular mechanisms underlying the coumarins' biological activity. The compounds are selected and grouped according to their cytotoxic, anticancer, antibacterial, antifungal, and miscellaneous effects.